Dog tags [large type] - Rosenfelt, David (Rosenfelt, David. Andy Carpenter novels., 2011)
A German shepherd police dog witnesses a murder and if his owner - an Iraq war vet and cop-turned-thief - is convicted of the crime, the dog could be put down. No one loves man's best friend more than attorney Andy Carpenter, and he decides to represent the poor canine. When he discovers that the dog and his owner have unwittingly become involved in a case of much larger proportions, Andy will need the help of the police-trained dog.